Indicators of the kinetic transfer of some parts of the body and its relationship to the amount of movement of the ball according to the law of collision when scoring in football - Selman Saleh, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The coordination of movement of the parts of the body leads to achieving the goal of the movement, and the correct assessment of the distance when scoring in football has a major role in the success of the scoring, from the body to the tool (the ball).